BS EN IEC 60512-27-200. Connectors for electrical and electronic equipment. Tests and measurements. Part 27-200. Additional specifications for signal integrity tests up to 2 000 MHz on IEC 60603-7 series connectors. Tests 27a to 27g (11th September 2020) - British Standards Institution,
No abstract available